SATELLITE MONITORING: SATELLITE MONITORING - Stoyanov, Stiliyan; Zhekov, Zhivko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
n the current paper, satellite methods for research of gas content of the atmosphere are presented. The stress is on the satellite methods and the measurement geometry. A generalized characteristic of the absorption specters of the atmospheric ozone and gases into the optic range is presented when research with land and satellite appliances and apparatuses. An evaluation of the satellite methods is made when measuring the content of small gases. Scientific results are presented which are received by satellite experiments and the perspectives of satellite research are laid down.